2010
DOI: 10.1051/0004-6361/200913825
|View full text |Cite
|
Sign up to set email alerts
|

The Hamburg/ESOR-process enhanced star survey (HERES)

Abstract: AstrophysicsThe Hamburg/ESO R-process enhanced star survey (HERES) V ABSTRACTAims. We present a detailed abundance analysis of a strongly r-process enhanced giant star discovered in the HERES project, HE 2327−5642, for which [Fe/H] = −2.78, [r/Fe] = +0.99. Methods. We determined the stellar parameters and element abundances by analyzing the high-quality VLT/UVES spectra. The surface gravity was calculated from the non-local thermodynamic equilibrium (NLTE) ionization balance between Fe i and Fe ii, and Ca i an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
86
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(94 citation statements)
references
References 127 publications
7
86
0
Order By: Relevance
“…There are larger scatters among the results of Th correlated with Ba and Sr, and usually the scatter comes from the unclear type stars, which indicates the existence of multiple nucleosynthesis prcesses. Scatter of [Ba/Fe] and [Sr/Fe] were also reported by other studies (McWilliam 1998;Norris et al 2001). All these elements follow similar abundance pattern as thorium as expected, and stars of the same enhancement type have quite consistent distribution, supporting that they might form from the materials experienced similar chemical enrichments.…”
Section: Correlation With Other Neutron Capture Elementssupporting
confidence: 84%
See 2 more Smart Citations
“…There are larger scatters among the results of Th correlated with Ba and Sr, and usually the scatter comes from the unclear type stars, which indicates the existence of multiple nucleosynthesis prcesses. Scatter of [Ba/Fe] and [Sr/Fe] were also reported by other studies (McWilliam 1998;Norris et al 2001). All these elements follow similar abundance pattern as thorium as expected, and stars of the same enhancement type have quite consistent distribution, supporting that they might form from the materials experienced similar chemical enrichments.…”
Section: Correlation With Other Neutron Capture Elementssupporting
confidence: 84%
“…It appears that among the r-process enhanced stars with measured Th or other actinide elements (e.g., U), except for an actinide normal group, which means no obvious enhancement of actinide element abundances with respect to the scaled solar r-process pattern, an actinide boost group (e.g., CS31082-001, HE1219-0312, CS30306-132) also came to be known, although the former group seems to be more common among r-process enhanced metal-poor stars (e.g., CS22892-052, CS29497-004). This imples that for elements in the range of Z ≥ 90, significantly different chemical yields might be produced due to the various conditions of the star formation regions (Hill et al 2002;Roederer et al 2009;Mashonkina et al 2010).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…With this correction, we derived the relative abundance [N/Fe] = −0.32. It is worth noting that several papers applied "solar oscillator strengths" of the NH molecular lines, where Kurucz (1993) log g f -values were reduced by a factor of 0.807 dex (Hill et al 2002), 0.4 dex (Aoki et al 2006;Hayek et al 2009;Mashonkina et al 2010), and 0.3 dex (Shavrina et al 1996;Johnson et al 2007). Cayrel et al (2004) and this paper.…”
Section: Lithium To Zincmentioning
confidence: 82%
“…Observations of MP halo stars appear to infer a distinct production mechanism for Sr-Zr and heavy elements beyond Ba in the early Galaxy (Aoki et al 2005;François et al 2007;Mashonkina et al 2007b). Mashonkina et al (2010) found a clear distinction in Sr/Eu abundance ratios between the r-II and r-I stars, namely, the r-II stars contain a low Sr/Eu abundance ratio at [Sr/Eu] = −0.92 ± 0.13, while the r-I stars have 0.36 dex higher Sr/Eu values.…”
Section: Introductionmentioning
confidence: 91%